Three embedded choral improvisation etudes - DiFebo, Jake, author; David, James M., advisor; Pendergast, Seth, advisor; Coffino, Kara, committee member (Colorado State University. Libraries, 2023)
Choral music educators often have to choose between sticking to their concert cycle or sacrificing some of that time to prioritize musical creativity. Teacher-Composers have recently worked to solve this issue by writing new works that scaffold the singers in the harmonic structure or rhythmic framework before calling for improvisation. Thus teachers can make low stakes musical creation part of the traditional performance. While structured improvisation is common within standard vocal jazz repertoire, a small percentage of high schools actually have vocal jazz programs – it is far more common to have a jazz band. In the name of equity and in order to help cultivate the creativity of young singers, they too must be actively engaged in meaningful musical creation. The following are three etudes each written to focus on a different aspect of vocal improvisation: Melodic choices in Living for the Now, Rhythmic in Pic-nic Tricks for Kicks, and Syllabic in Cognizant Consonance. The preceding sections of composed material scaffold the following improvisational sections, encouraging the singers to hone in on their choice-making.
Zip file contains supplementary video, no sound.
Keywords: curriculum; improvisation; vocal; embedded; composition; new music